ELIMED-ELIMAIA: The First Open User Irradiation Beamline for Laser-Plasma-Accelerated Ion Beams - Cirrone, Giuseppe A. P.; Petringa, Giada; Catalano, Roberto; Schillaci, Francesco; Allegra, Luciano; Amato, Antonino; Avolio, Renato; Costa, Michele; Cuttone, Giacomo; Fajstavr, Antonin; Gallo, Giuseppe; Giuffrida, Lorenzo; et al. (Frontiers in Physics, 2020)
The main effort of the laser-driven ion acceleration community is aimed at improving particle beam features (in terms of final maximum energy, particle charge, and beam divergence) and to demonstrate reliable approaches for use for multidisciplinary applications. An ion acceleration target area based on unique laser capabilities is available at ELI-Beamlines (Extreme Light Infrastructure) in the Czech Republic; it is called ELIMAIA (ELI Multidisciplinary Applications of laser-Ion Acceleration) and aims to provide stable and characterized beams of particles accelerated by high-power lasers to offer them to the user community for interdisciplinary studies. The ELIMAIA section dedicated to ion focusing, selection, characterization, and irradiation is named ELIMED (ELI MEDical and multidisciplinary applications). Thanks to ELIMED, very high-dose-rate (around Gy/min) controlled proton and ion beams, with energy levels ranging from 5 to 250 MeV, will be transported to an in-air section dedicated to absolute and relative dosimetry of the laser-generated ions. A transmission dual-gap air ionization chamber will allow an on-line, non-destructive characterization of the ion dose at the user sample irradiation point. The uncertainty in the final dose released onto the sample is expected to be well below 5%. An ELIMED radiobiology pilot experiment is scheduled for 2021, during which in-vitro cell irradiations will be carried out with well-controlled proton beams. In this work, the status of the ELIMED/ELIMAIA beamline will be described along with a complete definition of the main dosimetric systems and of their calibrations carried out at conventional accelerators.